Wheat (Triticum aestivum l.) production under drought and heat stress – adverse effects, mechanisms and mitigation: A review - El Sabagh, A. (2019)
Heat and drought stresses are the most important abiotic factors that reduce crops productivity by affecting various physiological and biochemical processes. Thus, selecting cultivars with better drought or heat stress tolerance or breeding for stress tolerance will be helpful in enhancing crop productivity under harsh environments. This review elaborates the physiological basis of high temperature and drought stress tolerance in wheat which can be used as selection criteria in wheat breeding program. In addition, some agronomic selection criteria which are valid and useful in selecting stress tolerant wheat species and cultivars. The review also discussed the valid usage of stress tolerance indices (such as mean productivity (MP), geometric mean productivity (GMP), yield index (YI), yield stability index (YSI), relative productivity (RP%), stress susceptibility index (SSI), and the tolerance index (TOL)) to scan the genotypes against drought and heat stress. Beside these, exogenous application of stress signaling compounds, osmolytes, or certain inorganic salts play a vital role for alleviating adverse effects of abiotic stresses for sustainable wheat production. In addition, applications for soil amendments will also helpful in increasing wheat crop productivity under stressful conditions. All these strategies may be helpful to meet the food demands of the increasing population.